Pengembangan Lembar Kegiatan Peserta Didik (LKPD) Berbasis Problem Solving pada Materi Virus untuk Kelas X SMA/MA - Desi Nurmayenti; Heffi Alberida; Fitri Arsih; Irdawati Irdawati (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2023)
LKPD (Student Activity Sheet) in student-centered learning serves as a guide for learning activities. Based on the results of observations and interviews with teachers at SMA AL-Istiqamah it is known that the LKPD in this school has not been adapted to the learning model used, therefore it needs to be developed. The purpose of this study was to develop problem solving based worksheets on viruses for class X SMA/MA. This type of research is development research using the 4-D model. The subjects of this study were 39 students of class X MIPA 1 SMA AL-Istiqamah. The product that is produced is a problem solving based LKPD on virus material. The validators consisted of two lecturers from the Department of Biology FMIPA UNP and one Al-Istiqamah High School Biology teacher. The research data is in the form of validation data and practicality of LKPD. Data analysis is in the form of descriptive statistics. The results showed that problem solving-based worksheets on virus material fulfilled the valid category with a validity value of 89.26% and practical with 88.45% practicality. It could be concluded that problem solving-based Student Activity Sheets were produced on virus material for class X SMA. Valid and practical /MA.